Characterization of the growth-related transcriptome in the Liver and Brain of mandarin fish (Siniperca chuatsi) through RNA-Seq analysis - Weidong Ding; Liping Cao; Zheming Cao; Xuwen Bing (Journal of Applied Animal Research)
The brain and liver of mandarin fish (Siniperca chuatsi) produce essential hormones for their growth and development. However, the mechanisms underlying the interplay of these hormones remain unclear. This study aimed to assess the slow – and fast-growing traits, including body weight and length of mandarin fish reared in a single pond. To compare the differentially expressed genes (DEGs) in slow – and fast-growing fishes, we performed RNA sequencing analysis. After assembling the clean reads, 192,280 transcripts and 100,416 unigenes were obtained. 344 and 845 DEGs in the brain and liver in the fast-and slow-growing group were annotated respectively. These DEGs were associated with signaling pathways involved in growth and development, such as AGE-RAGE, Transforming growth factor-β/Smad, Mitogen-activated protein kinase, Wingless/Integrated, and Insulin-like growth factor (IGF) 1. Furthermore, our fasting experiment revealed a concurrent decrease in body weight and the expression levels of genes related to the growth hormone (GH)/IGF system, alongside an increase in the insulin-like growth factor binding protein gene IGFBP3 expression. These findings suggest the GH/IGF system regulates body weight during fasting periods. The vast amount of transcriptome data generated in this study substantially expands the existing gene and genome resources for the growth traits of mandarin fish.